Política agraria y reparto de tierras en Colima, 1915-1935 - Ramírez Magallón, María de Jesús (Universidad Michoacana de San Nicolás de Hidalgo, 2011)
In Rosa's studies Congost,1 she begins with a declaration of intentions, because many bad experts are generated around the concepts "property and proprietor." In this case I serve myself as the example to point out that the motivation that he/she brought me to the topic was big, since questions that few people respond have existed and that in the measure in the one that I was comparing the experiences campiranas with the theoretical positionings that I ended up looking for in the Political Science, realized that the sector is dynamic that lives in constant tension and that the quantitative idea that we have on the agrarian question doesn't respond to the historical reality, neither to their multiple expressions. In this sense, the historical construction, related with the property of the earth is a constant in the work, agrarian titled Politics and allotment of lands in Colima, 1915-1935; because nevertheless I believed pertinent to leave of the structures outlined by the political economy, I saw myself in the necessity of energizing them, so that they responded to the subtle details that I am certain that they exist. It is this, together with the identification of political and economic nets, one of the variants that offers my work with relationship to what has already been made.

En los estudios de Rosa Congost,1 ella comienza con una declaración de intenciones, porque se generan muchos malos entendidos alrededor de los conceptos “propiedad y propietario”. En este caso me sirvo del ejemplo para señalar que la motivación que me trajo al tema fue grande, dado que han existido preguntas que pocas personas responden y que en la medida en la que fui comparando las experiencias campiranas con los posicionamientos teóricos que llegué a buscar en la Ciencia Política, me di cuenta que el sector es dinámico, que vive en constante tensión y, que la idea cuantitativa que tenemos sobre la cuestión agraria no responde a la realidad histórica, ni a sus múltiples expresiones. En este sentido, la construcción histórica, relacionada con la propiedad de la tierra es una constante en el trabajo, titulado Política agraria y reparto de tierras en Colima, 1915-1935; pues no obstante creí pertinente partir de las estructuras planteadas por la economía política, me vi en la necesidad de dinamizarlas, para que respondieran a los detalles sutiles que me consta que existen. Es esto, junto con la identificación de redes políticas y económicas, una de las variantes que ofrece mi trabajo con relación a lo que ya se ha hecho.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; IIH-M-2011-0011; Opción en historia de México; Política agraria; Reparto de tierras; Colima; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2410